Metabolic profiling of a range of peach fruit varieties reveals high metabolic diversity and commonalities and differences during ripening - Monti, Laura Lucía (2016)
Peach (Prunus persica) fruits from different varieties display differential organoleptic and nutritional properties, characteristics related to their chemical composition. Here, chemical biodiversity of peach fruits from fifteen varieties, at harvest and after post-harvest ripening, was explored by gas chromatography–mass spectrometry. Metabolic profiling revealed that metabolites involved in organoleptic properties (sugars, organic and amino acids), stress tolerance (raffinose, galactinol, maltitol), and with nutritional properties (amino, caffeoylquinic and dehydroascorbic acids) displayed variety-dependent levels. Peach varieties clustered into four groups: two groups of early-harvest varieties with higher amino acid levels; two groups of mid- and late-harvest varieties with higher maltose levels. Further separation was mostly dependent on organic acids/raffinose levels. Variety-dependent and independent metabolic changes associated with ripening were detected; which contribute to chemical diversity or can be used as ripening markers, respectively. The great variety-dependent diversity in the content of metabolites that define fruit quality reinforces metabolomics usage as a tool to assist fruit quality improvement in peach.